Comparing the Importance of Curriculum Integration from the point of view of Academic Staff of Tabriz University of Medical Sciences and University of Tabriz Faculty Members - Firooz Mahmoodi; Zeynab Cheraghi (Journal of Medical Education Development, 2017)
Background and Objective: The rapid expansion of knowledge and information, fragmentation and dispersion of various sectors of traditional curricula, and little connection with the real world have made learners pay more attention to the issue of integration in curricula. The aim of this study was to compare the viewpoints of academic staff of Tabriz University of Medical Sciences with the University of Tabriz about integration steps.